2015
DOI: 10.1007/s11695-015-1871-8
|View full text |Cite
|
Sign up to set email alerts
|

Is a Simple Food-Diverting Operation the Solution for Type 2 Diabetes Treatment? Experimental Study in a Non-Obese Rat Model

Abstract: A simple SJA, diverting the food and biliopancreatic secretion to the distal small bowel, was able to normalize both FBG levels and OGTT in a non-obese diabetic rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Others have reported improved glucose metabolism following PID in animal models and clinical studies involving patients. 6,7,15,16 It is clear that in the case of PPID, we observed a significant (and comparable to VSG) improvement in glucose tolerance despite a non-significant reduction in body fat. VSG and DPID improve glucose tolerance and cause profound reductions in body fat.…”
Section: Pid Results In Notable Improvement In Glucose Metabolismsupporting
confidence: 63%
See 3 more Smart Citations
“…Others have reported improved glucose metabolism following PID in animal models and clinical studies involving patients. 6,7,15,16 It is clear that in the case of PPID, we observed a significant (and comparable to VSG) improvement in glucose tolerance despite a non-significant reduction in body fat. VSG and DPID improve glucose tolerance and cause profound reductions in body fat.…”
Section: Pid Results In Notable Improvement In Glucose Metabolismsupporting
confidence: 63%
“…15,16 Body weight and fat mass loss relative to Sham has also been reported in animals. 7,15 Though notable improvements in glucose metabolism are observed after DJB, body weight and composition outcomes relative to Sham are not altered by this procedure. 19,25,26 These data support our findings that a duodenal component to the PID may render this operation less effective for weight loss.…”
Section: Dpid Induces Lower Body Weight and Fat Mass Relative To Sham And It Is Superior To Ppidmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, PSIB did not transect the jejunum, but only made a simple side-to-side anastomosis of the small bowel, which maintained the normal electrophysiology of the small bowel, enabling a certain amount of paraproperistalsis in the bypassed small bowel segments, with a much smaller amount of food regurgitation than that of the end-to-side anastomosis of JIB. Melissas et al [10] reported that simple side-to-side jejunoileal anastomosis (SJA) to transfer food and biliopancreatic secretions to the distal small bowel normalized FBG levels and OGTT in Goto Kakizaki rats. Therefore, we hypothesized that one of the reasons for the superior e cacy of PSIB over JIB in lowering blood glucose levels could be attributed to the side-to-side anastomosis, which eliminates the retrograde peristalsis of the bypassed small bowel segment, thereby reducing glucose absorption [11].…”
Section: Discussionmentioning
confidence: 99%